New sonographic marker of borderline ovarian tumor: microcystic pattern of papillae and solid components. (8th August 2019) - Timor‐Tritsch, I. E.; Foley, C. E.; Brandon, C.; Yoon, E.; Ciaffarrano, J.; Monteagudo, A.; Mittal, K.; Boyd, L.
ABSTRACT: Objective: To describe and evaluate the utility of a new sonographic microcystic pattern, which is typical of borderline ovarian tumor (BOT) papillary projections, solid component(s) and/or septa, as a new ultrasound marker that is capable of distinguishing BOT from other adnexal masses, and to present/obtain histologic confirmation. Methods: In this retrospective study, we identified women with a histologic diagnosis of BOT following surgical resection who had undergone preoperative transvaginal ultrasound (TVS) examination. All images were reviewed for presence or absence of thin‐walled, fluid‐filled cluster(s) of 1–3‐mm cystic formations, associated with solid component(s), papillary projections and/or septa. From the same cases, histopathologic slides of each BOT were examined for presence of any of these microcystic features which had been identified on TVS. To confirm that the microcystic TVS pattern is unique to BOTs, we also selected randomly from our ultrasound and surgical database 20 cases of epithelial ovarian cancer and 20 cases of benign cystadenoma, for review by the same pathologists. To confirm the novelty of our findings, we searched PubMed for literature published in the English language between 2010 and 2018 to determine whether the association between microcystic tissue pattern and BOT has been described previously. Results: Included in the final analysis were 62 patients (67 ovaries) with preoperative TVS and surgically confirmed BOT on pathologic examination. The mean patient age at surgery was 39.8 years. The mean BOT size at TVS was 60.7 mm. Of the 67 BOTs, 47 (70.1%) were serous, 15 (22.4%) were mucinous and five (7.5%) were seromucinous. We observed on TVS a microcystic pattern in the papillary projections, solid component(s) and/or septa in 60 (89.6%) of the 67 BOTs, including 46 (97.9%) of the 47 serous BOTs, 11 (73.3%) of the 15 mucinous BOTs and three (60.0%) of the five seromucinous BOTs. On microscopic evaluation, 60 (89.6%) of the 67 samples had characteristic 1–3‐mm fluid‐filled cysts similar to those seen on TVS. In seven cases there was a discrepancy between sonographic and histologic observation of a microcystic pattern. The 20 cystadenomas were mostly unilocular and/or multilocular and largely avascular. None of them or the 20 epithelial ovarian malignancies displayed microcystic characteristics, either on TVS or at histology. On review of 23 published articles in the English medical literature, containing 163 sonographic images of BOT, we found that, while all images contained it, there was no description of the microcystic tissue pattern. Conclusion: We report herein a novel sonographic marker of BOT, a 'microcystic pattern' of BOT papillary projections, solid component(s) and/or septa. This was seen in the majority of both serous and mucinous BOT cases. Importantly, based on comparison of sonographic images and histopathology of benign entities and malignancies, the microcystic appearance seems to be unique to BOTs. No similar description has been published previously. Utilization of this new marker should help to identify BOT correctly, discriminating it from ovarian cancer and benign ovarian pathology, and should ensure appropriate clinical and surgical management. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.